Short- and Long-Term Complications of Free Anterolateral Thigh Flap Reconstructions: A Single-Centre Experience of 92 Consecutive Cases. (8th March 2022) - Kidd, Thomas; Platt, Nicholas; Kidd, Daniel; Grobbelaar, Adriaan O.
Abstract : Background . The anterolateral thigh (ALT) flap has been amongst the most versatile components of the reconstructive surgeon's armamentarium. The authors utilise these flaps for a variety of reconstructive procedures including lower limb reconstruction; postsarcoma excision; and open fractures. Few studies have discussed the extent of recipient site morbidity and subsequent revisional procedures. We will report our experience of the ALT flap in 92 consecutive reconstructions with focus on recipient site complications and revisional procedures. Methods . Retrospective data collection was done from 92 patients who underwent ALT flap reconstruction—for various large soft tissue defects—at our unit at the Royal Free Hospital, London. We evaluated primary recipient site complications and the requirements for secondary operations after flap transfer. Results . All flaps survived with the exception of 3 cases (97% survival rate) in which irreversible venous thrombosis was encountered. 16 of 92 patients (17%) required a second recipient site operation for the following: 7 patients experienced major recipient site complications that warranted early return to theatre and 9 patients required a secondary revision thinning procedure(s). 8 of the 16 patients (50%) requiring second operations had construction on their lower leg/ankle/feet ( p value = 0.10). Conclusions . Our data demonstrated effective use of the ALT flap in the management of soft tissue reconstructive surgery. Partial flap necrosis was the main complication at the recipient site. In future work, secondary thinning procedures, particularly at the ankle/foot, should be separated from flap-specific complications. Furthermore, we demonstrate tailoring ALT thickness can be performed safely without compromising flap viability.